2011
DOI: 10.1088/0031-9155/56/15/001
|View full text |Cite
|
Sign up to set email alerts
|

Implications on clinical scenario of gold nanoparticle radiosensitization in regards to photon energy, nanoparticle size, concentration and location

Abstract: Gold nanoparticle (AuNP) radiosensitization represents a novel approach to enhance the effectiveness of ionizing radiation. Its efficiency varies widely with photon source energy and AuNP size, concentration, and intracellular localization. In this Monte Carlo study we explored the effects of those parameters to define the optimal clinical use of AuNPs. Photon sources included (103)Pd and (125)I brachytherapy seeds; (169)Yb, (192)Ir high dose rate sources, and external beam sources 300 kVp and 6 MV. AuNP sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
263
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(276 citation statements)
references
References 36 publications
10
263
0
3
Order By: Relevance
“…However, the clear trend is that sensitisation is seen to varying degrees with different cell types and GNPs preparations. Interestingly, the predicted dose enhancement based on total extra dose deposited due to gold being present, is orders of magnitude less than is actually observed (Lechtman et al, 2011). This is true even of MV X-rays where Compton interactions or pair production dominate and very little extra dose is expected.…”
Section: Discussionmentioning
confidence: 71%
“…However, the clear trend is that sensitisation is seen to varying degrees with different cell types and GNPs preparations. Interestingly, the predicted dose enhancement based on total extra dose deposited due to gold being present, is orders of magnitude less than is actually observed (Lechtman et al, 2011). This is true even of MV X-rays where Compton interactions or pair production dominate and very little extra dose is expected.…”
Section: Discussionmentioning
confidence: 71%
“…A number of Monte-Carlo simulations of possible clinical scenarios were carried out in the last few years to this purpose [see, for example, (17)(18)(19)(20)(21)(22)]. Such simulations are based on the fact that the transport of ionizing radiation in matter is of random nature and can be described using probabilistic models.…”
Section: The Vagaries Of Dose Enhancement Calculationsmentioning
confidence: 99%
“…So, due to the poorly formed tumor vasculature, the accumulation of unlabeled nanoparticles within the tumor can occur under passive targeting by increasing the effect of permeability and retention (EPR) 38 , 39 . Several other studies demonstrated the effects of GNPs in radiation treatment of the different tumors 33 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 …”
Section: Introductionmentioning
confidence: 99%